Sort by

- Relevance
- |Time

a[

**k**] = 1/ln(**k**)^ln(**k**) a[**k**+1] = 1/ln(**k**(1+1/**k**))^ln(**k**+1) = 1/( ln(**k**) + ln(1+1/**k**))^ln(**k**+1) = 1/ ( ln(**k**)^ln(**k**+1) ( 1+ (ln(1+1/**k**)/ln(**k**) )^ln(**k**+1) a[**k**]/a[**k**+1] =ln(**k**)(1+(ln...3 Answers · Science & Mathematics · 18/04/2007

"Solve for

**k**in terms of**k**" doesn't make sense:**k**=**k**is obvious. I...thing and see if we can get a cleaner statement of the relationship between x and**k**: log(base2)x+log(base2)(x+5)=**k**log(base2) [x(x+5)] =**k**{by properties of...2 Answers · Science & Mathematics · 19/10/2009

========= x^2 +

**k**+ 6 = kx +3x x^2 -x(**k**+3) + (**k**+6) = 0 The equation will have equal ... happens when the discriminant is zero. So, solve (**k**+3)^2 - 4(**k**+6) = 0**k**^2 + 6k + 9 - 4k - 24 = 0**k**^2 + 2k - 15 = 0 (**k**+5)(**k**-3...2 Answers · Science & Mathematics · 14/10/2012

This only true if

**K**is also a metric space. Otherwise there are counterexamples.... Now to prove the claim: Forward direction: Suppose**K**is compact and A = (x_n) is a sequence in**K**. We...2 Answers · Science & Mathematics · 16/10/2010

Hello, x³ – (

**k**+ 1)x + 2k = 0 = = = = = = = = = = = = = = = = = = = = = = Obviously, if**k**=0, we obtain... prime and**k**≠0: Then 2k has four divisors: 1, 2,**k**and 2k. Rational root theorem induce that if a rational root exists...2 Answers · Science & Mathematics · 10/12/2012

**k**=ideal gas constant**k**=universal gas constant**k**=constant proportional**k**=0.08205 L.atm/mol.**K**(if you're gonna use liter) or**k**=82.05ml.atm/mol.**K**(if you're gonna use ml)**k**is also be R it ...1 Answers · Science & Mathematics · 28/04/2008

... 6/(

**k**+1) - 1/(**k**) = 1 ← note:**k**≠ 0 or -1 or 6(**k**) - (**k**+1) = (**k**+1)(**k**) or 6k -**k**- 1 = k² +**k**or 0 = k² +**k**- 6k +**k**...4*3 ) ] / 2**k**= [ 4 ± 2√3 ) ] / 2**k**= 2 ± √3**k**= { 2 - √3, 2 + √3 }**k**~ { 0.2679, 3.7321 }3 Answers · Science & Mathematics · 11/09/2010

**k**= (**k**+15)/3*(**k**-1) ==> multiply both sides by 3(**k**-1) to get rid of fractions 3k(**k**-1) =**k**+15 ==> expand the LHS 3k^2-3k =**k**+15 ==> move everything to the LHS 3k^2-4k-15=0 actually this does...3 Answers · Science & Mathematics · 21/07/2007

2kx² - 12x + (

**k**+7) = 0 Solve for**k**b² - 4ac = 0 (b = -12, a = 2k and c =**k**...8 ..........-k² - 7k + 18 = 0 .......... k² + 7k - 18 = 0 ........ (**k**- 2) (**k**+ 9) = 0 ......**k**- 2 = 0..........................**k**+ 9 = 0**k**- 2 + 2 = 0 + 2...4 Answers · Science & Mathematics · 12/09/2010

Sources of Vitamin

**K**Vitamin**K**is found chiefly in leafy green ...of vitamin**K**.[7]. Some vegetable oils, notably soybean, contain vitamin**K**, but at levels that would require relatively large caloric consumption to meet the...9 Answers · Food & Drink · 07/03/2009

##### Ad

related to**K**